Beadchip molecular immunohematology toward routine donor and patient antigen profiling by DNA analysis - Edwards-Moulds, JoAnn; Ness, Paul M.; Sloan, Steve R. (Springer eBook., 2011)
First book on the market to be used for courses such as: Specialist in Blood Banking ("SBB") and other accreditation programs in molecular immunohematology for Hospital and Blood Bank Transfusion Services, Transfusion Medicine, and reference laboratories. Offers thorough review of molecular immunohematology, particularly the BeadChip technology developed by BioArray Solutions Draws from analyses and case studies around the world, detailing techniques used in many labs. We have entered the era of molecular immunohematology in which DNA is analyzed to predict red blood cell and platelet phenotypes. Indeed, many laboratories and blood banks across the world have already adopted and implemented molecular techniques. Some fear that serology is now becoming outdated, but immunohematology techniques often supplement the work of serologists, and several leading serology laboratories are the very same ones that were early adopters of molecular immunohematology. This book is a thorough review of molecular immunohematology and is aimed at anyone interested in how it is changing blood bank and transfusion medicine. BeadChip Molecular Immunohematology opens with a history of serology before it provides an overview of gene expression, how genetic variations translate into antigenic differences on the surfaces of cells, and techniques that have been developed to detect genetic variations. It then describes in detail the BeadChip technology developed by BioArray Solutions, the molecular immunohematology system that has been most widely adopted in blood blank laboratories. The remainder of the book focuses on analyses and case studies from around the world to describe how molecular immunohematology is being used in various settings for various purposes. It includes a discussion of the significant advances that have been made to incorporate Rh testing on the BeadChip platform as well as the potential use of that system